Development Of Learning Media Based On Silayar Folk Stories To Improve Reading Comprehension - Yulli Mulia Ningsih; Riris Nurkholidah Rambe (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This study aims to develop learning media based on Silayar folklore that are effective in improving students' reading comprehension skills. This learning media is designed to support a contextual and interesting learning process, by integrating local cultural values ??through folklore. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The results of the trial showed that this learning media is effective in improving students' reading comprehension skills, as evidenced by the increase in reading comprehension scores after using the media. In addition, this media also received a positive response from students and teachers, who stated that the use of folklore as learning material makes the learning process more interesting and meaningful. This conclusion encourages further research with the development of more interesting learning media. Overall, the use of learning media based on folklore makes a positive contribution to improving the reading comprehension skills of fifth grade elementary school students. Thus, this learning media based on Silayar folklore can be an innovative alternative to improve students' reading comprehension skills, while introducing and preserving local culture.